Development of a step-by-step design and simulation manual using Cadence SpectreRF - Koh, Chuan Seng. (2010)
Voltage-controlled oscillators (VCOs) are commonly found in wireless systems as well as in other communications systems that must tune across a band of frequencies. VCOs are available from a wide range of manufacturers in a variety of package styles and performance levels. Modern surface-mount and radio-frequency integrated-circuit (RFIC) VCOs, however, owe their heritage to engineering developments that began almost a hundred years ago. Improvements in VCO technology have continued throughout that time, yielding ever-smaller sources with enhanced phase noise and tuning linearity.